ASSESSMENT OF BODY FAT IN OBESE PATIENTS PREOPERATIVELY FOR BARIATRIC SURGERY - FERNANDEZ,Mônica (2016)
ABSTRACT Background: The study of body composition in patient candidates for bariatric surgery is directly related to the increase and distribution of body fat in the development of cardiovascular disease. Aim: To correlate anthropometric indicators and bioelectrical impedance in the assessment of body fat in female candidates for bariatric surgery. Methods: Cross-sectional, observational study of 88 women. The weight, height, body mass index and waist circumference data were evaluated in the anthropometric analysis. The body fat was determinate by bioelectrical impedance conducted according to the manufacturer´s recommended technique with a specific severe obesity formula. The patients were divided into two subgroups according to the average waist circumference and body mass index for better analysis of the results. Results: The group had a mean age of 39.7 years (±7.2), average weight of 125.6 kg (±16.2), mean body mass index of 48.7 kg/m2 (±6.4) and the mean waist circumference 137.6 cm (±12.4). Negative and significant relationship between BMI values waist circumference and resistance obtained by bioelectrical impedance ​​were found. By analyzing the two groups the mean BMI and waist circumference, a significant relationship was observed, ie, the higher the degree of obesity less resistance was obtained by bioelectrical impedance. The higher is the obesity the lower is value found for resistance. Conclusion: The increase of anthropometric indicators (BMI and waist circumference) determined reduction in resistance and reactance obtained by bioelectrical impedance analysis in obese women candidates to bariatric surgery.